PENERAPAN APLIKASI TAMBAHAN PENGHASILAN PEGAWAI NEGERI SIPIL DALAM MENINGKATKAN KINERJA PADA KANTOR CAMAT WUA-WUA KOTA KENDARI - Suriyani Bunga Batara; Muh. Nasir; Sakinah Maelani (Journal Publicuho, 2022)
This study aims to determine the application of additional income for civil servants in improving performance at the Wua-Wua sub-district office, Kendari City. The method used in this research is qualitative, there are six informants in this study. Data collection techniques are observation, interviews and documentation. The data analysis used is data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the Application of Additional Income for Civil Servants, namely; input activity in inputting activities, all employees can input their respective activities, it's just honesty that needs to be applied in inputting employee activities and constraints in inputting, namely network problems or signals that are not supportive, activity validation is carried out by their superiors and print out the TPPNS report, which is the admin's job to printed and brought to the Regional Personnel Agency (BKD) for disbursement. In measuring the performance of the State Civil Apparatus, the indicators in the research have been implemented.